Properties of various plants and animals feedstocks for biodiesel production - Karmakar, Aninidita; Karmakar, Subrata; Mukherjee, Souti (Bioresource technology, 2010)
As an alternative fuel biodiesel is becoming increasingly important due to diminishing petroleum reserves and adverse environmental consequences of exhaust gases from petroleum-fuelled engines. Biodiesel, the non-toxic fuel, is mono alkyl esters of long chain fatty acids derived from renewable feedstock like vegetable oils, animal fats and residual oils. Choice of feedstocks depends on process chemistry, physical and chemical characteristics of virgin or used oils and economy of the process. Extensive research information is available on transesterification, the production technology and process optimization for various biomaterials. Consistent supply of feedstocks is being faced as a major challenge by the biodiesel production industry. This paper reviews physico-chemical properties of the plant and animal resources that are being used as feedstocks for biodiesel production. Efforts have also been made to review the potential resources that can be transformed into biodiesel successfully for meeting the ever increasing demand of biodiesel production.